Soft Skill PENGARUH SOFT SKILL, HARD SKILL DAN MEDIASI BUDAYA ORGANISASI TERHADAP KAPABILITAS INOVASI DOSEN - Nur Layli Fatikhatun Nissa; Larassaty, Ayu Lucy (FEB Universitas Sam Ratulangi Manado, 2024)
This research aims to measure the influence of soft skills and hard skills on the innovative abilities of lecturers at Nahdlatul Ulama University Sidoarjo which is mediated by organizational culture. Implementing a type of quantitative research using purposive sampling by distributing questionnaires to PGSD lecturers at Nahdlatul Ulama University, Sidoarjo, which are then processed using SmartPLS. From the research results, it is known that soft skills influence organizational culture. Hard skills influence organizational culture. Organizational culture influences lecturers' innovation capabilities. The phenomenon in this research is how lecturers increase creativity and create new learning ideas that can enrich students' learning experiences